Characteristics and use of urban health indicator tools by municipal built environment policy and decision-makers: a systematic review protocol. Issue 1 (December 2017) - Pineo, Helen; Glonti, Ketevan; Rutter, Harry; Zimmermann, Nicole; Wilkinson, Paul; Davies, Michael
Abstract Background There is wide agreement that there is a lack of attention to health in municipal environmental policy-making, such as urban planning and regeneration. Explanations for this include differing professional norms between health and urban environment professionals, system complexity and limited evidence for causality between attributes of the built environment and health outcomes. Data from urban health indicator (UHI) tools are potentially a valuable form of evidence for local government policy and decision-makers. Although many UHI tools have been specifically developed to inform policy, there is poor understanding of how they are used. This study aims to identify the nature and characteristics of UHI tools and their use by municipal built environment policy and decision-makers. Methods Health and social sciences databases (ASSIA, Campbell Library, EMBASE, MEDLINE, Scopus, Social Policy and Practice and Web of Science Core Collection) will be searched for studies using UHI tools alongside hand-searching of key journals and citation searches of included studies. Advanced searches of practitioner websites and Google will also be used to find grey literature. Search results will be screened for UHI tools, and for studies which report on or evaluate the use of such tools. Data about UHI tools will be extracted to compile a census and taxonomy of existing tools based on their specific characteristics and purpose. In addition, qualitative and quantitative studies about the use of these tools will be appraised using quality appraisal tools produced by the UK National Institute for Health and Care Excellence (NICE) and synthesised in order to gain insight into the perceptions, value and use of UHI tools in the municipal built environment policy and decision-making process. This review is not registered with PROSPERO. Discussion This systematic review focuses specifically on UHI tools that assess the physical environment's impact on health (such as transport, housing, air quality and greenspace). This study will help indicator producers understand whether this form of evidence is of value to built environment policy and decision-makers and how such tools should be tailored for this audience. Systematic review registration N/A.